StyA1 and StyA2B from Rhodococcus opacus 1CP: a multifunctional styrene monooxygenase system - Tischler, Dirk; Kermer, René; Gröning, Janosch A D; Kaschabek, Stefan R; van Berkel, Willem J H; Schlömann, Michael (Journal of bacteriology, 2010)
Two-component flavoprotein monooxygenases are emerging biocatalysts that generally consist of a monooxygenase and a reductase component. Here we show that Rhodococcus opacus 1CP encodes a multifunctional enantioselective flavoprotein monooxygenase system composed of a single styrene monooxygenase (SMO) (StyA1) and another styrene monooxygenase fused to an NADH-flavin oxidoreductase (StyA2B). StyA1 and StyA2B convert styrene and chemical analogues to the corresponding epoxides at the expense of FADH2 provided from StyA2B. The StyA1/StyA2B system presents the highest monooxygenase activity in an equimolar ratio of StyA1 and StyA2B, indicating (transient) protein complex formation. StyA1 is also active when FADH2 is supplied by StyB from Pseudomonas sp. VLB120 or PheA2 from Rhodococcus opacus 1CP. However, in both cases the reductase produces an excess of FADH2, resulting in a high waste of NADH. The epoxidation rate of StyA1 heavily depends on the type of reductase. This supports that the FADH2-induced activation of StyA1 requires interprotein communication. We conclude that the StyA1/StyA2B system represents a novel type of multifunctional flavoprotein monooxygenase. Its unique mechanism of cofactor utilization provides new opportunities for biotechnological applications and is highly relevant from a structural and evolutionary point of view.